2021
DOI: 10.3390/nu13082565
|View full text |Cite
|
Sign up to set email alerts
|

Hydration, Eating Attitudes and Behaviors in Age and Weight-Restricted Youth American Football Players

Abstract: There is a paucity of research examining hydration and nutrition behaviors in youth American football players. A potentially unique risk factor are league restrictions based on weight (WR) or age (AR). The purpose of this study was to examine hydration status between WR and AR leagues. The secondary purpose was to describe eating patterns in players. An observational cohort design with 63 youth football players (10 ± 1 yrs, 148.2 ± 9.4 cm, 44.9 ± 15.3 kg) was utilized. Independent variables were league (AR (n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…This highlights the importance of raising awareness about hydration status among young athletes. Furthermore, 63 youth football players with physical activity were mildly hypohydrated in free-living conditions [ 45 ]. Research has demonstrated that dehydration impedes physical performance.…”
Section: Discussionmentioning
confidence: 99%
“…This highlights the importance of raising awareness about hydration status among young athletes. Furthermore, 63 youth football players with physical activity were mildly hypohydrated in free-living conditions [ 45 ]. Research has demonstrated that dehydration impedes physical performance.…”
Section: Discussionmentioning
confidence: 99%
“…39 To combat dehydration, fluids should be readily available for consumption before, during, and after activity sessions, and contrary to the routines of many youth athletes, activity sessions need to be separated further to maintain their normal level of hydration. [40][41][42][43] Moreover, drinking fluids ad libitum during practices is insufficient to prevent further dehydration. 41 Therefore, coaches should encourage regular fluid consumption to prevent further dehydration of their athletes as well as to maintain adequate hydration for optimal performance.…”
Section: Hydration Statusmentioning
confidence: 99%
“…A final example may be setting bodyweight targets, which could lead to athletes engaging in unhealthy weight loss behaviors. For example, 22% of youth American football players given bodyweight targets in order to be selected to compete were deemed to be at risk of abnormal eating behaviors, with eating binges, excessive exercise and drastic weight loss methods such as sauna use reported (61). Such body-mass manipulation can lead to dehydration that may affect performance in subsequent training activities (6), and similar thermal weight loss techniques have been described as “concerning” in combat sports (5).…”
Section: Issues and Challenges With Key Performance Indicatorsmentioning
confidence: 99%